Reproduction and diet of a population of Mabuya dorsivittata (Squamata, Scincidae) in Cordoba, Argentina - Aun, Liliana (2011)
The reproduction and diet were studied in Mabuya dorsivittata a viviparous lizard from Alto Alegre (Córdoba). The smallest female with yolking ovarian follicles measured (svl) 41 mm, and the smallest male with spermatozoa in the testes measures (svl) 31mm. The litter size was from five to ten embryos. A positive and significant correlation existed between the weight of the eggs or embryos and the reproductive state (B = 0,524, R = 0,254, P 0,001). In males there was a positive and significant correlation between the testicular volume and the reproductive state (R2 = 0,851, b= 0,929, P= 0,002). The mass of fat bodies in females and males was related with the reproductive period, especially in the females, diminishing in the final phases of embryo development, indicating a high energetic cost during the last months of embryonic growth. Regarding the diet, females fed mainly on soil Araneae as fundamental prey, Scarabeidae, Araneae (others) and Acridiidae as secondary prey, whereas males fed on Isopoda, Acridiidae and Araneae as fundamental prey and on Tettigonidae as secondary prey. There were significant differences in trophic selection among sexes.